Psychometric testing of Chinese version of screening tools (PASS) and GAD among perinatal population: hospital based evidence 2023 - Xiaoying Zhong; Mei He; Xiujing Guo; Xixi Li; Bangjun Wang; Changqing Pan; Rong Hu; Hongjing Wu (BMC Psychiatry)
Abstract Background Anxiety disorders are increasing worldwide, untreated anxiety is linked to maternal and child health outcomes. The purpose of this study is to test psychometric properties of the Perinatal Anxiety Screening Scale (PASS) among Chinese women. Methods The PASS was translated into Chinese following Beaton’s intercultural debugging guide. A total of 494 women in the antenatal and postnatal phase participated ( 268 antenatal and 186 postnatal ) were recruited between March 2023 and July 2023 from two hospitals in Sichuan Province, China. The instruments included the demographic characteristics form, PASS, Edinburgh Postnatal Depression Scale (EPDS), and Generalized Anxiety Disorder-7 (GAD-7). The confirmatory factor analysis (CFA), internal consistency reliability and convergent validity were assessed. Results The mean age of the participant was 31.67 years (SD = 3.78; range from 23 to 49). The CFA showed that four-factor model of the Chinese-PASS had an excellent fit to the data ( χ2 = 1481.2477; df = 425; χ2/df = 3.485; RMSEA = 0.071; CFI = 0.871; NNFI = 0.828; TLI = 0.859; and IFI = 0.871). The Cronbach’s alpha coefficient of total scale was 0.950, and the split-half reliability of total scale was 0.907. The PASS significantly correlated with EPDS (r = 0.732) and GAD-7 (r = 0.763). The area under the ROC curve for PASS scores was 0.91 (SE = 0.01; 95% CI = 0.89–0.94). At cut-off score of ≥ 19.5, the sensitivity was 0.87. The area under the ROC curve for GAD-7 scores was 0.89 (SE = 0.02; 95% CI = 0.86–0.92). At cut-off score of ≥ 3.5, the sensitivity was 0.82. Conclusions The result of this study show that the Chinese-PASS had a reasonably adequate validity and reliability and can be used to screen for anxiety disorder among women during the perinatal period.